La temporalité intergénérationnelle, une dimension incontournable des parcours - Emmanuelle Santelli (Temporalités)
This article considers the question of intergenerational temporality. Devised initially to analyse the trajectories of the descendants of North African immigrants in French society, intergenerational temporality appears to have a broader heuristic scope. To demonstrate this point, the author begins with a section devoted to the role of time in life course analysis. She describes how the concepts of time and trajectory are mobilized. In the second section, the author uses empirical examples to describe how contexts and their intergenerational dimensions are captured. In the third section, she builds upon the life course paradigm to show how, in her view, intergenerational temporality is a component of the principle of temporality. The way by which intergenerational temporality provides a means to capture both family history and social dynamics is represented in table form. To conclude, the fourth section seeks to demonstrate why intergenerational temporality is the key to understanding life courses. In doing so, the article offers an epistemological contribution to analyse the importance of the question of time, by proposing here to capture more fully the intergenerational dimension in the temporal approach.